Perbedaan Pembiayaan Model Bagi Hasil dan Non Bagi Hasil Terhadap Profitabilitas dan Resiko (Studi Kasus BMT Amanah Ummah) - Agustha, Ilham Nur; Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This research is conducted to identify the relationship between profit sharing financing, non-profit-sharing, risk, and profitability of the BaitulMaalwatanwil. While the purpose of this study was conducted to determine the difference between the two financing available in BMT Amanah Ummah Karah Surabaya branch (profit sharing and non-sharing).The method used in this study is qualitative approach, using the case study method. The collection of the data done by linking the questions asked, the data collected with the conclusions drawn from interviews with secretaries and marketing lending at headquarter of BMT Amanah Ummah Karah Surabaya branch.The results showed that non-profit-sharing financing have a higher level of profitability than the profit sharing financing. Meanwhile, from the level of risk, profit sharing financing have a higher degree of risk compare to non-profit sharing financing.